Stakeholder Model of Corporate Governance: Methodology for Rapid Assessment of the Impact of Macroeconomic Challenges - I. N. Tkachenkoa; M. A. Meteleva (Управленческие науки, 2024)
The global humanitarian and economic challenges facing Russian corporate structures today require not only a rethinking of the role of public institutions in the future fate of the national economy, but also unprecedented innovative development of mechanisms for making management decisions in conditions of limited time and information. Well-known and methodologically developed approaches need transformation and development in relation to new realities. Based on the competent opinion of Russian corporate management on the current situation in the business environment, voiced at the XII All-Russian Forum «Business Management: Adaptation to Challenges and Development», requirements for the transformation of the corporate governance model have been determined. The purpose of the study was to develop the methodology proposed earlier by the authors for assessing the stakeholder value of the corporate network of the ESG activities of the corporation in terms of the influence of macro-level factors on it, in particular, economic sanctions. The following methods were used as a methodological basis: network approach, methods of logical analysis, correlation and regression analysis, comparison, graphic visualization. The methodology presented in the article was tested on the example of PJSC Norilsk Nickel and the region of its presence – the Krasnoyarsk Territory, based on data from two periods – pre-crisis (2012–2018) and including the COVID‑19 pandemic and strengthening of foreign trade sanctions (2012–2021). The results showed the sensitivity of the stakeholder value model to changes in macro conditions, which confirms the validity of the methodology for solving problems of operational management of corporate processes. The prospects for the research lie in the area of expanding the composition of stakeholder groups, developing methods for establishing operational connections between them and their assessment.